Using the Reactions to Group Situations Test to profile higher education administrators relative to team behavior predisposition and demographics - Brauer, Douglas C., author; Harbour, Clifford P., advisor (Colorado State University. Libraries, 2007)
This study facilitated the development of a profile of the predisposition for team behavior for community college administrators on the path to, or having, membership in an executive leadership team (ELT). The profile was based on emotionality and work (EW) variables, as defined by Basic Assumption Theory. The EW data were collected using the Reactions to Group Situations Test (RGST). The profile consisted of EW variable data examined in conjunction with demographic variable data, which included age, gender, time at institution, time in position, position title, educational level, race/ethnicity, social class of origin, and ELT membership status. The RGST instrument was used to collect data from community college administrators from the State of Illinois. From this, insight was gained to better understand the community college administrators' predisposition for team behavior as a discovery research step intended to lead to the identification of potential developmental interventions for individuals and ELTs to facilitate high team effectiveness.
Keywords: executive leadership team; higher education; higher education administrators; leadership; RGST; reactions to group situations test; team behavior; community colleges; school administration; educational administration; community college education